Theoretical Studies on the Design of Benzo[1,2-c:4,5-c’]bis[1,2,5]selenadiazole Acceptor-Based Organic Dyes - Taylor Dorlus; Jing Wang; Jerzy Leszczynski (Crystals)
π-conjugated organic material, specifically, the modification of donor acceptor-based dyes, has gained significant attention over the years for its outstanding performance in efficient dye-sensitized solar cells (DSSCs) as well as contributing to overall economically sustainable solar cell technology. In the present study, density functional theory (DFT) and time-dependent DFT (TD-DFT) approaches were executed to investigate the impact of benzobisselenadiazole (BBSD) based organic dyes with interchangeable donor and acceptor units on their optical properties. Two spacers were selected from 27 π-linker models due to their better performance on the absorption spectra. A total of 200 BSSD dyes were designed based upon the above two selected spacers linking with various donors and acceptors. The corresponding structures and properties were theoretically analyzed by DFT/TDDFT methods. D10A8-16 and D10A6-17 show the best performance and may become the best candidates to be developed as efficient dye sensitizers for DSSCs. Our results showed that structural changes can effectively improve the optoelectronic properties of the designed BSSD dyes. This provides us with an economic and fast screening way for artificial design of new dyes.